between x = -3 and x = -2
in Algebra 1 Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

f(-3)=36-(-3)-3=36 and f(-2)=16-(-2)-3=15.

So we have two points (-3,36) and (-2,15). The average rate of change is the difference of the y coords divided by the difference of the x coords, to give us the slope=(15-36)/(-2-(-3))=-21/1=-21. This slope is the average rate of change between x=-3 and x=-2.

by Top Rated User (600k points)

Related questions

1 answer
1 answer
Welcome to, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
81,977 questions
86,376 answers
72,112 users